Nigerian bonny light crude oil induces endocrine disruption in male rats (2013)
Exposure to Nigerian bonny light crude oil (BLCO) in the southern part of Nigeria has been reported to be associated with reproductive toxicity, but there is paucity of information on its interference with steroidogenesis. This study investigated the influence of BLCO on testicular steroidogenesis and plasma levels of hormones from the pituitary and thyroid components of the brain–pituitary–testicular axis. Adult male Wistar rats were orally treated with BLCO dissolved in corn oil at 0, 200 and 800 mg/kg for 7 days. Immunoblot analysis revealed that BLCO exposure suppressed steroid acute regulatory protein and androgen-binding protein expression with concomitant decrease in 3b-hydroxysteroid dehydrogenase (HSD) and 17bhydroxysteroid dehydrogenase activities. BLCO exposure significantly decreased plasma concentrations of follicle-stimulating hormone, luteinizing hormone, prolactin and intratesticular testosterone, but elevated thyrotropin, triiodothyronine and thyroxine above the control values. The data presented herein indicate that undue exposure to BLCO has an inhibitory effect on testicular steroidogenesis. The underlying mechanisms for BLCO-induced testicular dysfunction may involve its disruptive effect on the brain–pituitary–testicular axis. These observations highlight the potential risk to public health for a population where, unfortunately, oil spillages occur frequently.